Improving Students' Problem Solving Abilities through the Application of Auditory Intellectually Repetition Model - Ismunandar, Denni; Rosyadi, Rosyadi; Nurafifah, Luthfiyati; Jofre, Ahmad (Pendidikan Matematika STKIP Kusuma Negara, 2022)
The purpose of this study is to know the improvement of students' problem solving ability through the Application of auditory intellectually repetition (AIR) model. This research method uses the quantitative method by taking one experimental class. Samples were assigned from one Public Vocational School in Indramayu, by a purposive technique, based on the selection of teaching teachers. They were from X TKJ2 consisting of 29 students. Data retrieval uses a pretest and posttest of problem solving abilities. Based on the results of data analysis: (i) the student's pretest got the lowest and highest score respectively 6 and 23, and the average was 14.42, (ii) the student's posttest got the lowest and highest score respectively 21 and 38, and the average was 31.17. The maximum score for the pretest and posttest is 40. Based on the hypothesis test using the t-test obtained the observation value of t was 6 and the critical value of t was 2.03, because of that the AIR model was effectively implemented in learning in the classroom. Furthermore, a gain score test was carried out, and then the results were obtained by using the AIR model to improve students' problem solving abilities.